Responsiveness to ripasudil may be a potential outcome marker for selective laser trabeculoplasty in patients with primary open-angle glaucoma - Taro Baba (Nature Portfolio, 2021)
Abstract We examined responsiveness to ripasudil as a potential factor for predicting the effect of selective laser trabeculoplasty (SLT) when performed for primary open-angle glaucoma (POAG). A total of 70 eyes with no history of glaucoma surgery underwent SLT between January 2015 and June 2019. Patients were divided into two groups, with an intraocular pressure (IOP) decrease of 15% or more due to ripasudil administration before SLT defined as the effective group, while an IOP decrease of less than 15% was defined as the non-effective group. Kaplan–Meier survival analysis was performed. A Cox proportional hazards model assessed the influence of baseline factors on the success. Of the 70 eyes evaluated, treatments were effective in 22 and non-effective in 48. Postoperatively, both groups exhibited IOP reductions for up to 24 months. Success ratios at 12 and 24 months after SLT were 43.5% and 18.5% in the effective versus 24.9% and 9.3% in the non-effective group, which were significantly higher in the effective group (P = 0.03). Presence of a ripasudil effective eye (P = 0.03) was associated with treatment success. Responsiveness to ripasudil may be useful in predicting the therapeutic effect of SLT.